An entomopathogenic fungus recently discovered to attack Amrasca biguttula biguttula (Hem.: Cicadellidae) in Benin: provisional identification and research to be undertaken - Silvie, P.J.; Lopez Llanders, A.; Yarou, B.; De Troij, A.; Goergen, G. (2023)
In June 2023, high populations of Amrasca biguttula were observed in Cotonou, Benin, infected by an entomopathogenic fungus on leaves of Abelmoschus esculentus (okra). This first reporting in Africa could be due to an Entomophthorale. Recommendations are given to better identify the fungus.